Number of Daily Peritoneal Dialysis Exchanges and Mortality Risk in a Chinese Population. Issue 2 (December 2018) - Yu, Xueqing; Chen, Jianghua; Ni, Zhaohui; Chen, Nan; Chen, Menghua; Dong, Jie; Chen, Limeng; Yu, Yusheng; Yang, Xiao; Fang, Wei; Yao, Qiang; Sloand, James A.; et al.
Background: We report outcomes on ≥ 4 compared with < 4 exchanges/day in a Chinese cohort on continuous ambulatory peritoneal dialysis (CAPD). Methods: Data were sourced from the Baxter (China) Investment Co. Ltd Patient Support Program database, comprising an inception cohort commencing CAPD between 1 January 2005 and 13 August 2015. We used cause-specific Cox proportional hazards and Fine-Gray competing risks (kidney transplantation, change to hemodialysis) models to estimate mortality risk on ≥ 4 compared with < 4 exchanges/day. We matched or adjusted for age, gender, employment, insurance, primary renal disease, size of CAPD program, year of dialysis inception, and treatment center. Results: We modeled 100, 022 subjects from 1, 177 centers over 239, 876 patient-years. Of these subjects, 43, 185 received < 4 exchanges/day and 56, 837 ≥ 4 exchanges/day. The proportion of patients on < 4 exchanges/day varied widely between centers. Those on < 4 exchanges/day were significantly older, more often female, of unknown employment, and from rural China. In the various models, ≥ 4 exchanges/day was associated with a significantly lower risk of death by 30% – 35% compared with < 4 exchanges/day. This beneficial effect was greatest in younger and rural patients. Conclusions: In this Chinese CAPD cohort, ≥ 4 exchanges/day was associated with significantly lower mortality risk than < 4 exchanges/day. Analyses are limited by residual confounding from unavailability of important prognostic covariates (e.g., comorbidity, socioeconomic factors) and data on residual renal function, peritoneal clearance, and transport status with which to judge the clinical appropriateness of CAPD prescription. Nonetheless, our study indicates this area as a high priority for further detailed study.